Rupture of Extensor Pollicis Longus Tendon Caused by Scaphoid Nonunion Advanced Collapse Wrist - Takahito Kojima; Masataka Yasuda; Shunpei Hama; Makoto Fukuda; Kenta Minato (Case Reports in Orthopedics)
We report the case of a 69-year-old male patient with extensor pollicis longus (EPL) tendon rupture associated with a scaphoid nonunion advanced collapse (SNAC) wrist. He could not actively extend the left thumb interphalangeal joint and visited our institution for an examination. Plain X-rays revealed advanced stage SNAC and an enlarged soft tissue shadow owing to dorsal ridge growth. The patient was diagnosed with EPL tendon subcutaneous rupture due to SNAC. During surgery, the EPL tendon was found to be absent, a proximal-type scaphoid nonunion was detected, and bone growth to the dorsal part of the dorsal ridge was observed. Considering that the EPL tendon rupture was associated with the bone growth, we performed scaphoid lunate advanced collapse (SLAC) reconstruction and extensor indicis proprius tendon transfer which needed a revision tendon surgery afterward. To the best of our knowledge, EPL tendon ruptures caused by SLAC or SNAC are considered rare and have not yet been reported.